Delirium awareness – Improving recognition and management through education and use of a care pathway - TAURO, RUBEN (BMJ Qual Improv Rep, 2014)
Delirium occurs in 10–20% of medical patients on admission and a further 10–30% develop delirium as an inpatient. Delirium is associated with increased length of stay, morbidity, mortality, and risk of institutional placement. There is poor knowledge of delirium recognition and management, and a need to raise awareness and training of all staff. NICE have produced guidelines for diagnosis, prevention and management of delirium. A retrospective departmental audit demonstrated that delirium was under-recognised i.e. only 5.7% of discharges in one year. A staff questionnaire revealed poor knowledge of types of delirium and a significant underestimation of prevalence, with poor identification of risk factors. A multi-professional group was formed to raise staff awareness and develop a care pathway for delirium. A 19 bed acute elderly care ward was identified for the project. Ward based and departmental educational meetings were held. A Trust based awareness programme was also provided. Information leaflets on delirium were produced for patients, carers and families and posters at ward level. Environmental changes (signage) at ward level were introduced to improve the environment for patients. A delirium care pathway was created to encourage documentation of mental score, assessment of delirium, review of reversible medical causes and a nursing care plan. This pathway was reviewed regularly on ward rounds and feedback given to staff present. Following these interventions the notes of 106 consecutive discharges were reviewed over an 11-week period. 99% of at risk patients were screened for delirium. 35% of patients were diagnosed with delirium increasing the recognition rate from 5.7%. There was significant improvement among the staff in recognizing and managing patients with delirium through the use of a delirium care pathway. Education improves understanding and awareness of delirium and a care pathway focuses attention on this area, improving patient safety and quality of care.